2010
DOI: 10.1146/annurev-resource-040709-135112
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Environmental Federalism

Abstract: This survey encompasses multiple areas. The theoretical literature on environmental federalism continues to expand in areas such as capital competition and political economy. On the empirical side, emphasis is put on the existence of strategic interaction among states, the effects of President Reagan's decentralization of environmental policy, and possible free-riding behavior. Moreover, the European Union is currently conducting a major policy experiment with its emissions trading scheme, which has implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 76 publications
0
27
0
1
Order By: Relevance
“…In addition, when resources are mobile, concerns have been raised that local jurisdictions might want to compete for those resources by setting lax local environmental regulations, thereby resulting in a "race to the bottom" in terms of environmental quality. A large literature exists on this type of interjurisdictional competition for resources (Oates 2002;Dijkstra and Fredriksson 2010), focusing primarily on stationary pollutants generated by production processes (rather than pollutants that cross boundaries or stem from consumption or use of a product, such as an automobile). Both the theoretical and empirical results on this are mixed.…”
Section: Economic Spillovers: Leakage and Interjurisdictional Competimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when resources are mobile, concerns have been raised that local jurisdictions might want to compete for those resources by setting lax local environmental regulations, thereby resulting in a "race to the bottom" in terms of environmental quality. A large literature exists on this type of interjurisdictional competition for resources (Oates 2002;Dijkstra and Fredriksson 2010), focusing primarily on stationary pollutants generated by production processes (rather than pollutants that cross boundaries or stem from consumption or use of a product, such as an automobile). Both the theoretical and empirical results on this are mixed.…”
Section: Economic Spillovers: Leakage and Interjurisdictional Competimentioning
confidence: 99%
“…For example, the early theoretical literature (Oates and Schwab 1988), which assumed perfectly competitive jurisdictions and no pollution spillovers, found that Tiebout-like competition would lead local jurisdictions to make efficient decisions about local environmental policies as they sought to balance the local benefits and costs of more stringent standards. However, relaxing these assumptions by, for example, allowing strategic interaction among jurisdictions can lead to standards that are too stringent or too lenient, depending on the policy instrument used by the local government, the timing of the moves by regulators and firms, and the ownership of the mobile resource (Dijkstra and Fredriksson 2010).…”
Section: Economic Spillovers: Leakage and Interjurisdictional Competimentioning
confidence: 99%
“…Oates and Schwab confirmed that it is possible for a decentralized environmental authority to be efficient, even with interjurisdictional competition for capital [35]. However, decentralization and the Tiebout model require numerous assumptions or conditions [39,40]:…”
Section: Decentralization Of Environmental Governancementioning
confidence: 99%
“…Innym, bardzo praktycznym rozwi zaniem w zakresie federalizmu rodowiskowego jest koncepcja federalizmu progresywnego. Oznacza ona okre lenie norm i wymogów minimalnych na poziomie centralnym z mo liwo ci zaostrzenia ich na szczeblu regionalnym (Dijkstra, Fredriksson, 2010).…”
Section: Federalizm Fiskalny I Rodowiskowyunclassified